A Study on the Implementation of Human Resource Analytics in the Bpo Industries Chennai - Elantheraiyan, P.; S.Anand, Mr. (International Journal of Engineering and Technology, 2018)
In todayâ€™s competitive business scenario it very hard to retain knowledge based professional in BPO industries due to various reasons most of the BPO industries have a huge attrition rate or employee turnover which in turn not only impacts the companyâ€™sÂ specific process but as a whole which might decelerate the companies performance in the galloping business scenario with respect to the competitors. Hence HR Analytics plays the pivotal role in retaining ,identifying and motivating the right spirited employees who can champion the companies business in an ascending node. HR analytics is new emerging lifeline in the field of HR , now a days most of the company donâ€™t treat employees like an asset theyÂ treat them as expenses to the company. Especially this kind of attitude is more prominent among the BPO industries hence the attrition rate always gears up at a much faster rate This HR Analytics paves the way for the BPO companies to change their view regardingÂ employees and treat them as investments.Â Â